A ABORDAGEM DO MODO SUBJUNTIVO EM LIVROS DIDÁTICOS DE LÍNGUA PORTUGUESA DO ENSINO FUNDAMENTAL: THE SUBJUNCTIVE MODE APPROACH IN PORTUGUESE LANGUAGE TEACHING BOOKS OF FUNDAMENTAL EDUCATION - Santos, Hugo Leonardo Gomes dos; Carvalho, Hebe Macedo de (WEB REVISTA SOCIODIALETO, 2020)
O modo subjuntivo tem chamado a atenção de pesquisadores, no âmbito da Sociolinguística, devido a sua alternância com modo indicativo. Levando em conta os estudos e os achados da Sociolinguística (ROCHA, 1997; MEIRA, 2006; CARVALHO, 2007; FAGUNDES, 2007; OLIVEIRA, 2007; BARBOSA, 2013; PIMPÃO, 2015, 2017; CARVALHO; PIMPÃO, 2016) sobre alternância dessas formas e as funções modais desempenhadas pelo modo subjuntivo, nosso objetivo é investigar a sua abordagem em uma coleção de livros didáticos de língua portuguesa do ensino fundamental (DELMANTO; CARVALHO, 2018a, 2018b) do Programa Nacional do Livro Didático (PNLD) do ano de 2020. Após a seleção das obras, fizemos o levantamento e a análise de dez questões acerca do uso do subjuntivo. Embora adote definições dicotômicas sobre os modos verbais, apontando para uma possível abordagem tradicional do subjuntivo, nas atividades analisadas, o subjuntivo assume, além da função modal de expressão de incerteza, a expressão de probabilidade, de possibilidade e de volição, abrindo novas perspectivas sobre o ensino do subjuntivo e contemplando alguns achados das pesquisas sociolinguísticas. ABSTRACT: The subjunctive mood has attracted the attention of researchers, within the scope of Sociolinguistics, due to its alternation with indicative mode. Taking into account the studies and findings of Sociolinguistics (ROCHA, 1997; MEIRA, 2006; CARVALHO, 2007; FAGUNDES, 2007; OLIVEIRA, 2007; BARBOSA, 2013; PIMPÃO, 2015, 2017; CARVALHO; PIMPÃO, 2016) on alternating these forms and the modal functions performed by the subjunctive mood, our objective is to investigate its approach in a collection of Portuguese textbooks of elementary school (DELMANTO; CARVALHO, 2018a, 2018b) of the Programa Nacional do Livro Didático (PNLD) of 2020. After selecting the textbooks, we surveyed and analyzed ten questions about the use of the subjunctive. Although adopting dichotomous definitions about verbal moods, pointing to a possible traditional approach to the subjunctive, in the activities analyzed, the subjunctive assumes, in addition to the modal function of expression of uncertainty, the expression of probability, possibility and volition, opening new perspectives on teaching the subjunctive and contemplating some findings of sociolinguistic researches. KEYWORDS: Portuguese textbook; BNCC; Linguistic analysis; Subjunctive mood.